Pengembangan augmented reality book berbasis situs peninggalan kebudayaan sebagai sumber belajar sejarah - Bashofi, Ferdinan (Universitas Negeri Malang, 2021)
Augmented Reality Book is the development of a book inspired by the development of Augmented Reality technology. A book that is developed combining books in the form of literacy works with the findings of archaeological relics created in 3D images to be displayed in books with the help of an android application. This research adheres to the development theory made by Plomp which consists of 1) Initial Phase, 2) Design Phase, 3) Product realization or manufacture stage, 4) Testing, assessment, and improvement phase, 5) Product testing phase. From the data on the results of filling in the research instrument in the form of a questionnaire, it was obtained that 80% of the student's response value or the percentage showed a positive value, as the assessment indicators were in good criteria, so a conclusion could be drawn that students were motivated by the use of learning resources Augmented Reality Book.DOI: http://dx.doi.org/10.17977/um022v6i12021p19